Предмет: Алгебра,
автор: Серегахор
4k -4y +4a +y=
3(k-6)-(-27+k)=
-2(k-a)-3(a+2k)=
5+3x+((2x-1)-3)=
Срочно помогите!
Ответы
Автор ответа:
0
4k -4y +4a +y=4к-3у+4а
3(k-6)-(-27+k)=3к-18+27-к=2к+9
-2(k-a)-3(a+2k)=-2к+2а-3а-6к=-8к-а
5+3x+((2x-1)-3)=5+3х+2х-1-3=5х+1
3(k-6)-(-27+k)=3к-18+27-к=2к+9
-2(k-a)-3(a+2k)=-2к+2а-3а-6к=-8к-а
5+3x+((2x-1)-3)=5+3х+2х-1-3=5х+1
Похожие вопросы
Предмет: Математика,
автор: user19059806474
Предмет: Математика,
автор: Ktoichiev87
Предмет: Алгебра,
автор: sultan081105
Предмет: Математика,
автор: Аноним
Предмет: Физика,
автор: solonskayadasha